2020
DOI: 10.1109/access.2020.2990949
|View full text |Cite|
|
Sign up to set email alerts
|

Notice of Violation of IEEE Publication Principles: A Big Data Framework to Identify Tourist Interests Based on Geotagged Travel Photos

Abstract: Understanding the interests of tourists is a key skill for attraction managers to prepare plans and make strategic decisions in tourism marketing. The rapid growth and spread of social media websites provide an information-rich channel from which tourism researchers and managers can collect a large amount of text-based reviews or comments and photos relating to the past travel experiences of users. The travel photos with geographic information are especially helpful in identifying the geographical location of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…This system can also be used to avoid traffic congestion around central attractions. Further advanced research can also be found in studies by Ameen et al ( 2020 ) and Zhong et al ( 2020 ).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…This system can also be used to avoid traffic congestion around central attractions. Further advanced research can also be found in studies by Ameen et al ( 2020 ) and Zhong et al ( 2020 ).…”
Section: Introductionmentioning
confidence: 86%
“…This system can also be used to avoid traffic congestion around central attractions. Further advanced research can also be found in studies by Ameen et al (2020) and Zhong et al (2020). Cesario et al (2017) stated that mobile devices are becoming more common, making it easier to collect data about how people move.…”
Section: Geotagged Photos Data Miningmentioning
confidence: 99%
“…based on Geographic Information Big Data With the development trend of information technology, many IT industries have added geographic information services, which can provide location services and navigation services. This service function is to search for geographic information through maps in the Internet [10]. Outdated data has not been eliminated and covered because of the emergence of new data.…”
Section: Research On the Development Of Tourism Economy In Sichuan Pr...mentioning
confidence: 99%
“…Multiple researchers have studied trajectory prediction of tourism over the past several years, and benefited from the rapid development of artificial intelligence and big data. In the work presented by Leung et al [2] and Zhong et al [3], tourists' behaviors and the potential attractions they are interested in are examined based on the geotagged photos shared on their social media. The feasibility, however, is heavily relied on the social habits of tourists, and the method does not apply to those who rarely post on media platforms.…”
Section: Introductionmentioning
confidence: 99%